Asset Market Participation and Portfolio Choice over the Life‐Cycle - FAGERENG, ANDREAS; GOTTLIEB, CHARLES; GUISO, LUIGI (Journal of Finance, 2017)
ABSTRACT Using error‐free data on life‐cycle portfolio allocations of a large sample of Norwegian households, we document a double adjustment as households age: a rebalancing of the portfolio composition away from stocks as they approach retirement and stock market exit after retirement. When structurally estimating an extended life‐cycle model, the parameter combination that best fits the data is one with a relatively large risk aversion, a small per‐period participation cost, and a yearly probability of a large stock market loss in line with the frequency of stock market crashes in Norway.